Fotografias escolares: a leitura de imagens na história da escola primária - Souza, Rosa Fátima de [UNESP] (Setor de Educação da Universidade Federal do Paraná, 2001)
This research consists in photograph reading, more specifically, school photographs related to primary teaching in the city of Campinas, between 1897 and 1950. It is based on a heritage constituted of 55 images that analyzes four categories of photographs: school architecture, student classes, teaching body and school activities, these categories illustrate the discourse about school, human contexts and social relations revealed by those images. The text also focuses the iconography documentation relevance for History of Education research, specially, about educational institutions.

Este estudo compreende a leitura de fotografias, especificamente, fotografias escolares referentes ao ensino primário na cidade de Campinas, no período de 1897 a 1950. Com base em um acervo constituído de 55 imagens, analisa quatro categorias de fotografias: arquitetura escolar, classes de alunos, corpo docente e atividades escolares; assinalando o discurso sobre a escola, os contextos humanos e as relações sociais reveladas pelas imagens. O texto destaca, também, a relevância da documentação iconográfica para o estudo da História da Educação, em especial, o estudo das instituições educativas.
School Photographs: the image reading in the history of primary school
Keywords: Image reading; Fundamental School History; School photographs; Iconography sources; Leitura de imagens; História da Escola Primária; Fotografias escolares; Fontes iconográficas